Subclinical responses in healthy cyclists briefly exposed to traffic-related air pollution: an intervention study. - Jacobs, Lotte; Nawrot, Tim S.; Geus, Bas de; Meeusen, Romain; Degraeuwe, Bart; Bernard, Alfred; Sughis, Muhammad; Nemery, Benoit; Panis, Luc Int (BioMed Central, 2010)
Numerous epidemiological studies have demonstrated adverse health effects of a sedentary life style, on the one hand, and of acute and chronic exposure to traffic-related air pollution, on the other. Because physical exercise augments the amount of inhaled pollutants, it is not clear whether cycling to work in a polluted urban environment should be encouraged or not. To address this conundrum we investigated if a bicycle journey along a busy commuting road would induce changes in biomarkers of pulmonary and systematic inflammation in a group of healthy subjects. Therefore, 38 volunteers (mean age: 43 ± 8.6 years, 26% women) cycled for about 20 minutes in real traffic near a major bypass road (road test; mean UFP exposure: 28,867 particles per cm3) in Antwerp and in a laboratory with filtered air (clean room; mean UFP exposure: 496 particles per cm3). The exercise intensity (heart rate) and duration of cycling were similar for each volunteer in both experiments. Exhaled nitric oxide (NO), plasma interleukin-6 (IL-6), platelet function, Clara cell protein in serum and blood cell counts were measured before and 30 minutes after exercise. The results show that traffic-related exposure to particles during exercise caused a small increase in the distribution of inflammatory blood cells in healthy subjects. The health significance of this isolated change is unclear.
Keywords: Individualverkehr; Fahrradverkehr; Stadtverkehr; Untersuchung; Gesundheitsrisiko; Luftverschmutzung